"I'm not your reality show:" Perspectives of bereaved mothers' engagement with the news media to advance drug policy reform - Heather Morris; Petra Schulz; Emily Jenkins; Rebecca J Haines-Saah; Elaine Hyshka (Elsevier, 2021)
North America's overdose crisis is one of the most urgent public health issues of our time and parents bereaved from substance use are a prominent voice within the news media. To date, however, the experiences of bereaved mothers who have shared their stories with the media has not been well-documented, leaving a significant gap in our understanding of their political advocacy efforts.In 2017, we conducted qualitative interviews with 43 mothers across Canada who participated in drug policy advocacy following the substance-related death of their child. We used a narrative interview approach and thematic analysis to distill key themes in recounting bereaved mothers' stories of engaging with reporters, their perspectives on media representation and the personal impacts of sharing their stories with news media.Participants viewed the news media as powerful allies in educating the public, changing attitudes, and ultimately influencing policy in support of people who use substances. However, there was a personal cost that accompanied this media advocacy which included the potential for sensationalism, news media complacency, insensitive comments by journalists, and having one's story misrepresented.Our study highlights the complex relationship between mothers bereaved by substance use and the news media who hold tremendous power in framing their stories. By examining bereaved mothers as social movement actors and reflecting on the structural context in which news stories are delivered, we outline strategies to ensure parents bereaved by substance use can safely share their stories with media and continue their work in countering stigma and misinformation.